THE IMPACT OF SELECTED PORT PERFORMANCE INDICATORS ON ECONOMIC GROWTH IN NIGERIA, FROM 1995-2022 - IREJEH, Enaikpobomene Mina, SILE, Alex Akpoboloemi (Nigerian Journal of Management Sciences, 2025)
The impact of selected port performance indicators on economic growth in Nigeria. Data sourced from Nigeria Ports Authority’s(NPA) operational bulletin were analyzed using multiple regression model. It was observed that among CTP, GRT, STT and NOB, GRT and STT were found to have negative impact on Nigerian economy while CTP and NOB has positive impact on Nigerian economy. The study suggests that since vessel GRT has a positive impact on Nigeria's economy, it should serve as the foundation for determining port dues.
Keywords: GDP; cargo throughput; terminal; port authorities; port reform and turnaround time